PENERAPAN METODE THINK PAIR AND SHARE PADA PEMBELAJARAN MENULIS CERITA PENDEK SISWA SMK - Musthofa, Nadia Hudzaifah; Herlina, Sherly; Isnaini, Heri (IKIP Siliwangi, 2019)
The research is motivated by the researcher's curiosity about the process and results of improving students' skills in short story writing skills. What is the process and results of students' ability to write short story texts, namely by applying the think pair and share method in the learning process? This study aims to determine the process and results of short story text production in class XI students using the think pair and share method. The method used in this study is the quasi-experimental design method. The sample used in this study is class XI, with 25 students. Data collection techniques using the initial test and final test. Based on the results of research students' ability to write short story texts before using the think pair and share method obtained an average initial test score of 47 and after using the think pair and share method obtained an average final test score of 59.84. The results of the ability to write short story texts increased, so conclusions can be drawn using the think pair and share method in class XI can improve students' ability to write short story texts.